The role of lecturer personality on student performance: A self-study - Madolo, Y.; Thengimfene, A. (South African Journal of Higher Education, 2025)
This study investigates the role of lecturer personality on student performance. Lecturer personality is considered to be an important factor in determining the quality of the teaching and learning experience for both students and lecturers. It is suggested that a lecturer’s personality can have a major impact on the way students learn, as well as their overall learning experience. The focus of this article will be on a selected lecturer from a selected South African higher education institution (HEI). This study explores the effects of this lecturer's personality on their student’s performance. It examines the factors that contribute to the student's success to becoming a junior lecturer, led by the lecturer’s modelling of professionalism, enthusiasm, passion, accessibility and approachability, amongst other factors. To accelerate the conceptual debates of this article, qualitative research methodology is employed alongside the Social Cognitive Theory. Scholars note that there is a reciprocal effect between personal, environmental and behaviour factors that affect learning outcomes. This is the reason why this theory is employed in this research about the personality of this lecturer. Consequently, findings are that positive personality traits of a lecturer model good behaviour and encourage good performance towards students.